Kesan pertukaran gunatanah pertanian kepada keadaan sosioekonomi petani di kawasan pesisir Jawa Timur Indonesia - Suprajaka,; Ratnawati Yuni Suryandari, (Faculty of Social Sciences and Humanities, UKM,Bangi, 2007)
There has been a dramatic change in the agricultural sector in Indonesia during the last 34 years (1971-2005). The contribution of the agricultural sector to the Gross National Product (GNP) has decreased dramatically while that of the industrial sector has increased significantly. The structural shift from agriculture to industry and other non-agricultural uses is vividly manifested by the rapid conversion of farm land to urban uses with some unsettling consequences on the farming households and communities. This paper examines how this structural change has affected the villagers of Gresik, Sidoarjo, and Surabaya in the province of East Java. It was found that the economic structural change has destabilised the farming sector and led to a downfall in the living standard of farmers as they found themselves having to cope with drastic changes in their pattern of employment, social structures,community values and cultural traditions